PERBEDAAN PERSEPSI MAHASISWA AKUNTANSI TERHADAP ETIKA PENYUSUNAN LAPORAN KEUANGAN - Anwar, Yulianti; Amarullah, Fitriany (UI Scholars Hub, 2006)
One of the goals of accounting education in Indonesia is to introduce the stu dents to the ethics and values of accounting profession. This research focused on the effectiveness of accounting curriculum in developing students ’responsibility towards the financial statement s users. We find that accounting students oppose earnings management more strongly than do students from other disciplines, even though there are not any significant differences in their view of financial report ethics. This similar view on ethics also occurs between the new accounting students and senior accounting students. These results show that there are needs to reform the account ing curriculum - particularly in Indonesia - to emphasize more on ethics and values of the accounting profession.